THE INFLUENCE OF GENDER ON LEFT VENTRICULAR MECHANICS IN HYPERTENSIVE PATIENTS. (June 2018) - Tadic, M.; Cuspidi, C.; Celic, V.; Ivanovic, B.; Pencic, B.; Grassi, G.
Abstract : Objective: The aim of this study was to evaluate the influence of gender on left ventricular (LV) mechanics in hypertensive individuals. Design and method: This cross-sectional study included 198 untreated hypertensive subjects and 107 normotensive controls who underwent 24-hour ambulatory blood pressure monitoring and comprehensive two-dimensional echocardiographic examination including strain assessment. Results: There was no difference in 24-h blood pressure between hypertensive men and women. LV mass index was significantly higher men than in women in hypertensive and normotensive group. Hypertensive men and women had significantly lower 2D LV global longitudinal, circumferential and radial strains than their normotensive counterparts. LV global longitudinal strain was lower in hypertensive men than in women (−20.2 ± 2.3 vs. −18.8 ± 2.0, p < 0.01). LV global circumferential strain was also worse in hypertensive men than in men (−21.4 ± 2.9 vs. −19.5 ± 2.5, p < 0.01). The difference in LV radial strain was not discovered between hypertensive women and men. Assessment of layer-specific LV strain showed that endocardial and mid-myocardial longitudinal and circumferential strains were significantly lower in hypertensive population and especially in hypertensive men comparing with hypertensive women. Furthermore, LV twist was significantly higher in hypertensive women than in hypertensive men (20.6 ± 6.8 degree vs. 21.6 ± 7.3 degree, p = 0.02). Female gender and arterial hypertension, as well as their interaction, were associated with LV hypertrophy, reduced LV global longitudinal strain and increased LV twist. Conclusions: LV longitudinal and circumferential strains were significantly reduced in hypertensive patients. Endo- and mid-myocardial LV layers were particularly influenced by arterial hypertension. However, hypertensive women suffered more significant changes in LV longitudinal strain and LV twist than hypertensive men.